Public engagement in smart city development: Lessons from communities in Canada's Smart City Challenge - Goodman, Nicole; Zwick, Austin; Spicer, Zachary; Carlsen, Nina (The Canadian geographer, 2020)
Quality of life is often touted as the main benefit of building smart cities. This, however, raises questions about the extent to which the public is engaged as part of the “smart” development process, particularly given the significant financial investments often required to meaningfully design smart city projects. To better understand approaches to public engagement in the context of smart city development, we draw upon three selected finalists of Infrastructure Canada's Smart City Challenge, which invited municipalities, regional governments, and Indigenous communities to enter a competition where the winning proposals would be awarded federal financial grants to complete their projects. Prizes of $5 million, $10 million, and $50 million were awarded. Specifically, we compare the public engagement experiences of the Mohawk Council of Akwesasne (Quebec), the City of Guelph, and the Region of Waterloo. We carried out semi‐structured interviews and reviewed documents in each community to better understand how finalists in each category engaged residents in proposal development. The paper addresses how communities are approaching public engagement in smart city development and the implications of these approaches. We conclude that, despite earnest attempts to publicly engage and become citizen‐centric, municipal governments continue to see civic participation as a top‐down tool. Key Messages The Smart City Challenge's focus on citizen engagement highlights tension in municipal smart city design processes between top‐down and bottom‐up policymaking. Using the IAP2 Spectrum for Public Participation to evaluate proposals of three finalist communities suggests varied approaches to engaging residents in smart city design. We conclude that, despite earnest attempts to publicly engage and become citizen‐centric, municipal governments continue to see civic participation as a top‐down tool. La participation des citoyens au développement de la ville intelligente: les leçons du concours canadien sur les villes intelligentes La qualité de vie est souvent perçue comme étant le principal avantage de la mise en place des villes intelligentes. Toutefois, ceci soulève des questions sur la nature de la participation des citoyens à ce processus, en raison des investissements financiers importants requis pour concevoir les projets de ville intelligente. Pour mieux comprendre les approches à l'égard de la participation dans le contexte du développement de la ville intelligente, nous avons étudié les projets des trois finalistes sélectionnés lors du concours sur les villes intelligentes d'Infrastructure Canada, Rappelons que les propositions gagnantes se voyaient accorder des subventions financières fédérales pour réaliser leurs projets. Des prix de 5, 10 et 50 millions de dollars ont ainsi été attribués. Cet article évalue la façon dont les collectivités abordent la participation des citoyens dans le développement de la ville intelligente et les implications des différentes approches utilisées. Dans ce contexte, nous comparons les expériences de participation publique du Conseil mohawk d'Akwesasne, au Québec, de la Ville de Guelph et de la région de Waterloo. Nous avons effectué des entretiens semi‐directifs et analysé des documents dans chaque collectivité pour mieux comprendre la façon dont les finalistes ont mobilisé les résidents dans le développement de la proposition. Nos résultats montrent que malgré les tentatives sincères d'impliquer la population et d'adopter une approche centrée sur les citoyens, les administrations municipales continuent de considérer la participation civique comme un outil allant du haut vers le bas.